The chaperone‐like protein Cdc48 regulates ubiquitin‐proteasome system in plants. (2nd June 2021) - Rosnoblet, Claire; Chatelain, Pauline; Klinguer, Agnès; Bègue, Hervé; Winckler, Pascale; Pichereaux, Carole; Wendehenne, David
Abstract: The degradation of misfolded proteins is mainly mediated by the ubiquitin‐proteasome system (UPS). UPS can be assisted by the protein Cdc48 but the relationship between UPS and Cdc48 in plants has been poorly investigated. Here, we analysed the regulation of UPS by Cdc48 in tobacco thanks to two independent cell lines overexpressing Cdc48 constitutively and plant leaves overexpressing Cdc48 transiently. In the cell lines, the accumulation of ubiquitinated proteins was affected both quantitatively and qualitatively and the number of proteasomal subunits was modified, while proteolytic activities were unchanged. Similarly, the over‐expression of Cdc48 in planta impacted the accumulation of ubiquitinated proteins. A similar process occurred in leaves overexpressing transiently Rpn3, a proteasome subunit. Cdc48 being involved in plant immunity, its regulation of UPS was also investigated in response to cryptogein, an elicitor of immune responses. In the cell lines stably overexpressing Cdc48 and in leaves transiently overexpressing Cdc48 and/or Rpn3, cryptogein triggered a premature cell death while no increase of the proteasomal activity occurred. Overall, this study highlights a role for Cdc48 in ubiquitin homeostasis and confirms its involvement, as well as that of Rpn3, in the processes underlying the hypersensitive response. Abstract : The chaperone‐like Cdc48 regulates the cellular ubiquitinome and the proteasome in Nicotiana tabacum .